Evaluating the Potential of Dragon Fruit Cultivation in Banyuwangi District Based on Land Suitability - Romadhona, Sukron; Mutmainnah, Laily (Journal of Soilscape and Agriculture, 2024)
Among the horticulture commodities with development potential are fruit plants. Purposive sampling was the method used for sampling. With the exception of land uses like mining and settlements, sample points were chosen depending on land use. Each unit of land map created by land resource surveying and mapping activities has features, such as soil characteristics and physical environment features, that can be specifically defined as land characteristics. The purpose of this study is to investigate how suitable the terrain is for growing dragon fruit in the Banyuwangi Regency. This study used a survey methodology with land units serving as the analytical unit. Land units for this study were derived from the slope and overlap of land use maps. With an area coverage of 251,527 Ha, or 42.6%, the majority of Banyuwangi Regency is classified as having land suitability class S1 (very suitable), meaning that it does not have significant barriers to sustainable use or only minor ones that have no discernible impact on production or require an increase in input. Thus, it is critical to conduct this research in order to accurately evaluate the appropriateness of the site and enable the implementation of optimal land management strategies that will boost dragon fruit yield and lower production costs